2015
DOI: 10.1371/journal.ppat.1005332
|View full text |Cite
|
Sign up to set email alerts
|

Mono-ubiquitylated ORF45 Mediates Association of KSHV Particles with Internal Lipid Rafts for Viral Assembly and Egress

Abstract: Herpesviruses acquire their envelope by budding into the lumen of cytoplasmic membrane vesicles. This process is initiated by component(s) on viral particles, which recognize the budding site where the viral glycoproteins are present and recruit cellular cargo transport and sorting machinery to the site to complete the budding process. Proteins in the tegument layer, connecting capsid and envelope, are candidates for the recognition of budding sites on vesicle membrane and induction of budding and final envelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…2E, bottom-left panel). Consistent with the mainly cytoplasmic nature of tegument acquisition and envelopment of KSHV virions (52,58), only the cytosolic intron-less circ-vIRF4 ( Fig. 2E) was incorporated into KSHV particles (Fig.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…2E, bottom-left panel). Consistent with the mainly cytoplasmic nature of tegument acquisition and envelopment of KSHV virions (52,58), only the cytosolic intron-less circ-vIRF4 ( Fig. 2E) was incorporated into KSHV particles (Fig.…”
Section: Resultssupporting
confidence: 67%
“…Our cytoplasmic/nuclear fractionation experiments showed that circ-vIRF4.IR localizes to the nucleus and was not found in virus particles whereas the exon-only form was cytoplasmic and retained in the virion tegument. This is consistent with herpesvirus tegumentation and the envelopment maturation that occurs in the cytoplasmic compartment (52,58). circPANs and circK7.3s are also packaged into viral particles; however, given the high number and different sizes of circRNAs from these regions, we were unable to determine whether only cytoplasmic forms of these circRNA are incorporated into the KSHV virion.…”
Section: Kshv Circpans Are Inducible Whereas Circ-virf4 Is Constitutisupporting
confidence: 65%
“…ORF45 also interacts with another tegument protein, ORF33, and plays a crucial role in efficient production of KSHV viral particles (15). Most recently, ORF45 was shown to mediate association of KSHV particles with internal lipid rafts for viral assembly and egress (20).…”
mentioning
confidence: 99%
“…It can associate with the ubiquitin-specific protease USP7 and stabilize ORF33 and ORF36 (15,16). Monoubiquitinated ORF45 mediates the association between KSHV virus particles and lipid rafts for virus assembly and egress (17); it also interacts with kinesin-2 (13). However, with low sequence homology between EBV BKRF4 and KSHV ORF45, the amino acid sequences in the interacting domains with those partners are not well conserved in EBV BKRF4.…”
Section: Discussionmentioning
confidence: 99%